A spatial accommodation by neighboring cells is required for organ initiation in arabidopsis - Vermeer, Joop E. M.; Maizel, Alexis (Science, 2014)
Make Way for the Emerging Rootlet Plant cells are immobilized by their rigid cells walls, and the root endodermal cell layer maintains a impervious perimeter seal made of an indigestible irregular polymer. Despite these mechanical obstacles, lateral root primordia, which initiate in the deep layers of the root, manage to break through to the surface. Vermeer et al. (p. 178; see the cover) used live-tissue imaging and genetics to show that signals are exchanged between the root primordium and the handful of cells overlying it, which then cave in on themselves to open up a channel for the growing root primordium. Lateral root formation in plants can be studied as the process of interaction between chemical signals and physical forces during development. Lateral root primordia grow through overlying cell layers that must accommodate this incursion. Here, we analyze responses of the endodermis, the immediate neighbor to an initiating lateral root. Endodermal cells overlying lateral root primordia lose volume, change shape, and relinquish their tight junction-like diffusion barrier to make way for the emerging lateral root primordium. Endodermal feedback is absolutely required for initiation and growth of lateral roots, and we provide evidence that this is mediated by controlled volume loss in the endodermis. We propose that turgidity and rigid cell walls, typical of plants, impose constraints that are specifically modified for a given developmental process. Localized disruption of surrounding plant cell walls paves the way for lateral root development. Localized disruption of surrounding plant cell walls paves the way for lateral root development.
Gesehen am 08.05.2017